Síntese e caracterizações estruturais, morfológicas e magnéticas de nanocristais de FeMnO3 através do método sol-gel - Wesley Jose Mariano de Oliveira (2025)
The versatility of nanostructured materials has driven research in various technological fields. In this scenario, the FeMnO3 compound stands out for its promising applications in superparamagnetic materials, oxidation catalysis, and thermistors, in addition to its potential for sensors and lithium-ion batteries. With the aim of exploring these characteristics, FeMnO3 was synthesized as a nanocomposite using the sol-gel method via the Pechini route. The synthesis was carried out in an aqueous solution and at low temperature, which ensured a safe and effective process. The well-defined stoichiometry employed in the synthesis corroborated the confirmation of the compound's formation. The material's properties were systematically investigated, allowing for the precise determination of its composition and the evaluation of its properties through a set of complementary characterization techniques. Mössbauer spectroscopy and Rietveld refinement of X-ray diffraction data indicated a predominance of bixbyite (Fe0,25Mn0,75)2O3, with a proportion of 94%, in addition to a minor hematite phase (6%). Both FeMnO3 and hematite phases were confirmed by transmission electron microscopy and Raman spectroscopy. Magnetic measurements indicated a paramagnetic-ferrimagnetic transition in the major phase. Information obtained by magnetic resonance showed spin glass behavior on the surface, where a transition from paramagnetic to spin glass behavior was evidenced in the (Fe0,25Mn0,75)2O3 nanoparticle system. UV-Vis spectroscopy yielded a result consistent with a semiconductor material profile, showing a band gap of approximately 2.87 eV.